Reliability and Utility of Measures of Academic Progress (MAP) Test and Its Impact on Students' Learning: A Study in an American Curriculum School in Dubai - El Dor, Rana (2019)
Education has been given a major focus by educators and educational authorities in the United Arab Emirates (UAE) since the launch of the National Agenda (NA) by His Highness Sheikh Mohammad Bin Rashid Al Maktoum in 2010. Accordingly, the education reform started to pave its way towards internationalism and national emulousness. Educational authorities were established to contribute to this reform. All Dubai private schools are supervised and followed up closely and regularly by the Knowledge and Human Development Authority (KHDA) to ensure they are on the right track towards the change in education and towards meeting the targets of the National Agenda. This study aimed at investigating the reliability and utility of Measures of Academic Progress (MAP) testing and its impact on students’ learning. MAP testing was mandated by the KHDA for all American curriculum schools based on the National Agenda Parameter (NAP). MAP is used to benchmark students’ performance in schools following the American curriculum as it is aligned with the American curriculum standards. The researcher used actual MAP data from students’ scores, conducted surveys to students, and led interviews with both teachers and leaders in order to investigate how the school is using and benefiting from MAP testing and to test the impact this standardized test has on students’ learning. The study concluded that MAP testing allows for students’ academic progress. However, due to not utilizing MAP effectively and authentically in terms of modifying instructions to meet the needs of students, the test was not reliable and was found to have no impact on students’ learning. Also, findings emphasized the need for professional development for teachers on MAP testing and its resources in order to equip them with the needed strategies to benefit from this well designed and beneficial standardized assessment.